Student Perceptions of the Effectiveness of E-Learning in Higher Education: A Comparative Study of Two Universities in Indonesia and Malaysia - Maujud, Fathul; Nurman, Muhammad; Harun, Makmur; Rahman, Zidan Fitrayadi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This study examines students’ perceptions of the effectiveness of e-learning in higher education, focusing on the use of Learning Management Systems (LMS) at two universities in Indonesia and Malaysia. The research investigates how e-learning impacts lecture delivery and its overall effectiveness in promoting student engagement and learning outcomes. The study population includes students from the Arabic Language Education Program at a university in Indonesia and the Islamic History and Language Programs at a university in Malaysia, for the 2023-2024 academic year. A random sampling technique was employed, and the sample size was determined using the Slovin formula. Data were collected through questionnaires, observations, and interviews. Data analysis involved calculating the average score of questionnaire responses, which were then presented using tables and graphs. The findings indicate that students from both universities perceive e-learning as highly effective. This suggests that the use of LMS as an instructional tool is viewed positively by students and is considered an effective method for enhancing learning experiences in higher education. The results highlight the potential of e-learning platforms to support academic engagement and improve learning outcomes. The study has significant implications for the continued development of e-learning strategies and offers valuable insights for refining the implementation of online learning environments in higher education. Abstrak: Penelitian ini mengkaji persepsi mahasiswa terhadap efektivitas e-learning dalam pendidikan tinggi, dengan fokus pada penggunaan Sistem Manajemen Pembelajaran (LMS) di dua universitas di Indonesia dan Malaysia. Penelitian ini menyelidiki bagaimana e-learning mempengaruhi penyampaian materi kuliah dan efektivitas keseluruhannya dalam meningkatkan keterlibatan mahasiswa dan hasil pembelajaran. Populasi penelitian ini mencakup mahasiswa dari Program Pendidikan Bahasa Arab di sebuah universitas di Indonesia dan Program Sejarah dan Bahasa Islam di sebuah universitas di Malaysia, pada tahun akademik 2023-2024. Teknik pengambilan sampel yang digunakan adalah sampel acak, dan ukuran sampel ditentukan dengan menggunakan rumus Slovin. Data dikumpulkan melalui kuesioner, observasi, dan wawancara. Analisis data dilakukan dengan menghitung skor rata-rata dari jawaban kuesioner, yang kemudian disajikan dalam bentuk tabel dan grafik. Hasil analisis menunjukkan bahwa mahasiswa dari kedua universitas memandang e-learning sebagai sangat efektif. Hal ini menunjukkan bahwa penggunaan LMS sebagai alat pembelajaran dipandang positif oleh mahasiswa dan dianggap sebagai metode yang efektif dalam meningkatkan pengalaman belajar di pendidikan tinggi. Hasil penelitian ini menyoroti potensi platform e-learning dalam mendukung keterlibatan akademik dan meningkatkan hasil pembelajaran. Penelitian ini memiliki implikasi penting untuk pengembangan strategi e-learning yang berkelanjutan dan memberikan wawasan berharga untuk menyempurnakan penerapan lingkungan pembelajaran daring di pendidikan tinggi.